The Influence of Determinats on CO2 Emission in Indonesia for a Decade - Wahyudi, Heru; Gunarto, Toto; Ciptawaty, Ukhti; Aida, Neli; Yunita, Rily; Putri, Resha Moniyana (International Journal of Energy Economics and Policy, 2024)
This study aims to see the effect of GDP per capita, income inequality, and population on CO2 emissions in Indonesia from 1990-2021. This research uses a descriptive quantitative method. The data used is secondary data, in the form of annual data for 32 years. The analytical method used is the error correction model (ECM) to see the short and long-term effects between the independent variable and the dependent variable. The results of this study indicate that GDP per capita has a positive and significant effect on Indonesia, both in the short term and in the long term. The income inequality variable has a positive and insignificant effect on CO2 emissions in Indonesia in the short term. Meanwhile, in the long term, income inequality has a negative and insignificant effect on CO2 emissions in Indonesia. The population variable has an insignificant negative effect on CO2 emissions in Indonesia in the short term. However, in the long term, the population significantly affects CO2 emissions in Indonesia.